Humor As Coping Mechanism In John Green’s The Fault In Our Stars - Rangga Putra Sobhita; Hujuala Rika Ayu (SM Institute, 2026)
Humor has increasingly been recognized as an adaptive psychological strategy that promotes emotional resilience and mental well-being. However, studies examining humor as a psychological defense mechanism in literary works remain limited. This study aims to investigate how humor functions as a psychological defense mechanism in John Green's The Fault in Our Stars and to examine the differences in the use of humor by Hazel Grace Lancaster and Augustus Waters based on Sigmund Freud's Relief Theory. This research employed a qualitative descriptive approach using close reading to analyze selected dialogues and narrative descriptions containing humorous expressions. The findings reveal that humor performs three major psychological functions: releasing psychic tension, protecting the ego from emotional distress, and enabling the characters to confront illness and mortality with dignity and emotional stability. Furthermore, Hazel predominantly employs irony, sarcasm, and metaphor as self-protective strategies, whereas Augustus utilizes wit, exaggeration, and playful conversation to reduce anxiety, strengthen interpersonal relationships, and sustain hope. These findings confirm that humor operates as a mature psychological defense mechanism rather than mere entertainment. The study concludes that Freud's Relief Theory effectively explains the adaptive psychological function of humor in the novel. The findings contribute to psychoanalytic literary criticism by demonstrating that humor serves as an important coping strategy for maintaining emotional resilience and may provide a theoretical reference for future interdisciplinary studies integrating literature and psychology.